2019
DOI: 10.3390/pathogens8040190
|View full text |Cite
|
Sign up to set email alerts
|

Trypanosomatids in Small Mammals of an Agroecosystem in Central Brazil: Another Piece in the Puzzle of Parasite Transmission in an Anthropogenic Landscape

Abstract: We surveyed infection by Trypanosoma spp. and Leishmania spp. in small wild mammals from Cumari, Goiás State aiming to investigate the diversity of trypanosomatid in a modified landscape of the Brazilian Cerrado (and possible infection overlapping with canids from the same area). Blood, skin, spleen, and liver samples were collected for parasitological, serological, and molecular assays. Gracilinanus agilis was the most abundant species (N = 70; 48.6%) and it was the only one with patent parasitemia. Character… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 59 publications
0
16
0
1
Order By: Relevance
“…Positive hemocultures were detected in dogs, L. vetulus and C. thous, and it has been shown that these animals share at least one DTU of T. cruzi (TcIII) [ 10 ]. Although we were not able to distinguish the genotype/s involved (TcIII/TcV), previous studies using RFLP-PCR in samples from this two hoary foxes confirmed the infection by DTU TcIII [ 11 ], a genotype also found in marsupials ( Gracilinanus agilis ) from the same area [ 31 ]. Considering the pattern observed for experimentally infected domestic dogs, someone can expect that both wild and domestic canids from the area present a short period of patent parasitemia during the initial phase of infection (rarely demonstrated by positive hemocultures in this study), followed by a later phase with undetectable parasitemia, even in reinfections [ 39 ].…”
Section: Discussionmentioning
confidence: 54%
See 4 more Smart Citations
“…Positive hemocultures were detected in dogs, L. vetulus and C. thous, and it has been shown that these animals share at least one DTU of T. cruzi (TcIII) [ 10 ]. Although we were not able to distinguish the genotype/s involved (TcIII/TcV), previous studies using RFLP-PCR in samples from this two hoary foxes confirmed the infection by DTU TcIII [ 11 ], a genotype also found in marsupials ( Gracilinanus agilis ) from the same area [ 31 ]. Considering the pattern observed for experimentally infected domestic dogs, someone can expect that both wild and domestic canids from the area present a short period of patent parasitemia during the initial phase of infection (rarely demonstrated by positive hemocultures in this study), followed by a later phase with undetectable parasitemia, even in reinfections [ 39 ].…”
Section: Discussionmentioning
confidence: 54%
“…Both T. cruzi and Leishmania spp. infect wild and domestic canids at Limoeiro region, besides small mammals [ 31 ], and maintenance of these parasites by canids occurs despite the low rate of positive parasitological assays. Canids probably become infected through their exposure and consumption of infected vectors and prey.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations